ANALISIS AWAL KEBUTUHAN SISWA DAN GURU DALAM PENGEMBANGAN MODUL P5 BERBASIS LITERASI OCEAN DENGAN INTEGRASI KONTEKS KEMARITIMAN - M. Jaya Adi Putra; Mauliatun Nisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The conservation of the sea in North Rupat Island, Bengkalis Regency, Riau Province, faces significant challenges due to climate change and human activities. This study aims to analyze the needs of students and teachers in developing the Pancasila Student Profile Strengthening (P5) Project Module based on ocean literacy, with a focus on environmental understanding and marine conservation. The methodology employed is a qualitative approach with interviews and observations of the principal, teachers, and 4th-grade students of SDN 3 North Rupat. Data indicate that the school and teachers have a good understanding of ocean literacy and are committed to integrating it into the curriculum, although there are challenges regarding resources and support. Students demonstrate high awareness of the importance of maintaining sea cleanliness and are actively involved in conservation activities. In conclusion, despite facing some challenges, there is a strong commitment from the school, teachers, and students to support and enhance ocean literacy education and marine conservation in North Rupat.